Pembentukan Karakter Religius, Disiplin, dan Mandiri Siswa Taman Kanak-Kanak dalam Budaya Begibung pada Suku Sasak - Wahyuni, Indriwati; Winata, Aliahardi; Candra; Isnaini; Saddam; Nizaar, Muhammad (Al-Riwayah : Jurnal Kependidikan, 2024)
"Begibung," a communal dining tradition long practiced by the Sasak community, has now become the focus of research in the context of character formation among students at kindergarten. The research adopts a qualitative descriptive approach, with the study subjects comprising 20 students, 4 educators, and the head of the kindergarten. Research instruments include observation sheets, questionnaires, and interview guidelines, utilizing the Miles and Huberman method for data analysis to attain a comprehensive understanding of the effects of the communal dining program. The questionnaire comprises 5 items assessing religious character, 5 items for discipline, and 7 items for independence. Research findings indicate that the "Begibung" program in kindergarten effectively enhances religious character, achieving a commendable 89%. This outcome reflects the program's success in reinforcing religious values among students. Discipline character, reaching 74%, demonstrates a contribution in shaping student discipline through established rules. The independence character, marked at 65%, presents an opportunity for future enhancement in developing students' self-reliance, with a particular focus on personal initiative. The "Begibung" program in kindergarten proves to be highly effective in shaping the religious, disciplinary, and independent characters of students. This research makes a positive contribution to understanding the potential of the "Begibung" program as a character formation strategy in kindergarten.